The Past Perfect in Cypriot and Standard Greek: Innovation because or irrespective of contact? - Stavroula Tsiplakou; Spyros Armostis; Spyridoula Bella; Dimitris Micheloudakis; Amalia Moser (Language Variation - European Perspectives VII: Selected Papers from the Ninth International Conference on Language Variation in Europe (IClaVE 9), Malaga, June 2017, 2019)
The Cypriot Greek koine displays structural innovations, arguably as a result of prolonged contact with Standard Greek (SG), the ‘H’ variety in the diglossic context of the Greek Cypriot speech community. Periphrastic perfect forms are among such innovations. As regards the Past Perfect, in Standard Greek it has the principal reading of past in the past, as well as a remote past use; in contrast, the Cypriot Greek Past Perfect is largely interchangeable with the Aorist (Simple Perfective Past) and it may be deployed for pragmatic purposes, e.g. to mark an important point in a narrative, possibly due to its relative formality. In recent work it was claimed that this innovation is specific to Cypriot Greek. This paper revisits this hypothesis on the basis of the observation that Standard Greek also seems to display partly similar patterns. Using naturalistic data and data from a grammaticality judgement task, we explore (a) whether such variation is sociolinguistically conditioned and (b) what the semantics and pragmatics of the innovative Past Perfect are in each variety.